Gender and disruptions in family routines and stress amid COVID-19 - Saxena, Mamta; Shedlock, Dorothy J.; Gold, Zachary S. (Frontiers in Communication, 2023)
Initiation and maintenance of structure in family routines have universally been a gendered realm. Young girls in traditional cultures (non-industrialized) share in household chores, e.g., caregiving responsibilities for young and old. Likewise, females in industrialized nations such as the US, also act as kin-keepers, i.e., someone who maintains emotional connections among family members and fulfills their needs through routines and structure. Family researchers have suggested that initiation and maintenance of structure in family routines are vital, making the role of female family members essential. Evidence indicates that consistency and structure in family routines are associated with better developmental outcomes among members and family stability. Additionally, family routines can enhance the predictability of household situations, cohesion among members, and feelings of security. COVID-19 led to the "pausing" of the world's activities, mandating individuals to stay home, even for employment and education. The disrupted established family routines and dramatically increased workloads and stress. The current study surveyed US households about the impact of COVID-19 on changes in family routines, their related perceptions to the disruptions in routines, and related stress. Data indicated that both males and females were equally affected by changes in routines, perceptions of disruptions, and high-stress levels. However, because males and females spend time on different activities, it may lead to gender differences in potential physical and mental health issues post-COVID. Additionally, quantitative data was supplemented with qualitative gender-based narratives to establish descriptive evidence for differences in daily routines and stress.